Histological subtypes of lung cancer in Chinese women from 2000 to 2012 - Zou, Xiao Nong (Thorac Cancer, 2014)
BACKGROUND: The aim of the study was to characterize the histological and epidemiological features of lung cancer in Chinese women. METHODS: Demographic and histological information on female lung cancer cases identified during 1 January 2000 through 31 December 2012 from the Cancer Hospital of the Chinese Academy of Medical Sciences were collected. The International Classification of Diseases for Oncology system was used to classify the histological subtypes. Relative frequencies (RF) were estimated for major histological subtypes and compared by the years of diagnosis and birth, and among residential areas. Statistical differences were tested for RFs in the time periods with a trend test and with Pearson Chi square tests for distribution. RESULTS: Of 7070 female Chinese lung cancer cases, the major histological subtypes were adenocarcinoma (ADC) 65.79%; squamous cell carcinoma (SCC) 10.21%; small cell cancer 8.12%; large cell carcinoma, 2.79%; and adeno-squamous carcinoma (ASC), 2.19%. ADC increased, with RFs from 46.72% in the cases identified in 2000–2002 to 76.49% in 2011–2012 (Z = 16.998, P < 0.0001); SCC decreased from 15.69% to 5.97% (Z = −8.750, P < 0.0001). Compared to the cases identified in 2000–2006, the age-adjusted RFs of ADC in 2007–2012 consistently increased in all study areas. CONCLUSION: The significant increase of ADC of the lung in Chinese women suggests that a persistently strong exposure to potential carcinogens in the Chinese population should be further and fully investigated.